Evolution of secondary metabolites from an ecological and molecular phylogenetic perspective - Wink, M.
Secondary metabolites, at least the major ones present in a plant, apparently function as defence (against herbivores, microbes, viruses or competing plants)and signal compounds (to attract pollinating or seed dispersing animals). They are thus important for the plant's survival and reproductive fitness. Secondary metabolites therefore represent adaptive characters that have been subjected to natural selection during evolution. Molecular phylogenies of the Fabaceae, Solanaceae and Lamiaceae were reconstructed and employed as a framework to map and to interpret the distribution of some major defence compounds that are typical for the respective plant families; quinolizidine alkaloids and non-protein amino acids for legumes; tropane and steroidal alkaloids for Solanaceae, and iridoids and essential oils for labiates. The distribution of the respective compounds appears to be almost mutually exclusive in the families studied, implying a strong phylogenetic and ecological component. However, on a closer look, remarkable exceptions can be observed, in that certain metabolites are absent (or present)in a given taxon, although all the neighbouring and ancestral taxa express (or do not express, respectively)the particular trait. It is argued that these patterns might reflect differential expression of the corresponding genes that have evolved earlier in plant evolution. The inconsistent secondary metabolite profiles mean that the systematic value of chemical characters becomes a matter of interpretation in the same way as traditional morphological markers. Thus, the distribution of secondary metabolites has some value for taxonomy but their occurrence apparently reflects adaptations and particular life strategies embedded in a given phylogenetic framework.
Keywords: SECONDARY METABOLITES; ECOLOGICAL FUNCTION; DEFENCE; ATTRACTION; MOLECULAR PHYLOGENY; FABACEAE; LAMIACEAE; SOLANACEAE; CHEMOTAXONOMY